Inhibition of Heat Shock Protein 90 Attenuates the Damage of Blood-Brain Barrier Integrity in Traumatic Brain Injury Mouse Model - Jia-ming Zhang (Oxidative Medicine and Cellular Longevity, 2022)
Heat shock protein 90 (HSP90) is widely found in brain tissue. HSP90 inhibition has been proven to have neuroprotective effects on ischemic strokes. In order to study the role of HSP90 in traumatic brain injury (TBI), we carried out the present study. A novel inhibitor of the HSP90 protein, 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DA), has been investigated for its function on the blood-brain barrier (BBB) damage after traumatic brain injury (TBI) in mouse models. These C57BL/6 mice were used as a TBI model and received 17-DA (0.1 mg/kg/d, intraperitoneally) until the experiment ended. To find out whether 17-DA may protect against TBI in vitro, bEnd.3 cells belonging to mouse brain microvascular endothelium were used. The HSP90 protein expressions were raised after TBI at the pericontusional area, especially at 3 d. Our study suggested that 17-DA-treated mice improved the recovery ability of neurological deficits and decreased brain edema, Evans blue extravasation, and the loss of tight junction proteins (TJPs) post-TBI. 17-DA significantly promoted cell proliferation and alleviated apoptosis by inhibiting the generation of intracellular reactive oxygen species (ROS) to downregulate cleaved caspase-3, matrix metallopeptidase- (MMP-) 2, MMP-9, and P-P65 in bEnd.3 cells after the injury. As a result, we assumed that the HSP90 protein was activated post-TBI, and inhibition of HSP90 protein reduced the disruption of BBB and improved the neurobehavioral scores in a mouse model of TBI through the action of 17-DA, which inhibited ROS generation and regulated MMP-2, MMP-9, NF-κB, and caspase-associated pathways. Thus, blocking HSP90 protein may be a potential therapeutic strategy for TBI.